Characterization of a new (Z)-3:(E)-2-hexenal isomerase from tea (Camellia sinensis) involved in the conversion of (Z)-3-hexenal to (E)-2-hexenal. (30th July 2022) - Chen, Cong; Yu, Fei; Wen, Xinli; Chen, Shuna; Wang, Kaixi; Wang, Feiquan; Zhang, Jianming; Wu, Yuanyuan; He, Puming; Tu, Youying; Li, Bo
Highlights: Contents of (Z)-3-hexenal and (E)-2-hexenal increased after tea leaves were torn. (Z)-3:(E)-2-hexenal isomerase (CsHI) was identified for the first time in C. sinensis. CsHI expression was regulated by multiple abiotic stresses such as low temperature. CsHI regulated the ratios of (Z)-3-hexenal and (E)-2-hexenal in tea leaves. Abstract: Two major green leaf volatiles (GLVs) in tea that contribute greatly to tea aroma, particularly the green odor, are (E)-2-hexenal and (Z)-3-hexenal. Until now, their formation and related mechanisms during tea manufacture have remained unclear. Our data showed that the contents of (E)-2-hexenal and (Z)-3-hexenal increased more than 1000-fold after live tea leaves were torn. Subsequently, a new (Z)-3:(E)-2-hexenal isomerase (CsHI) was identified in Camellia sinensis . CsHI irreversibly catalyzed the conversion of (Z)-3-hexenal to (E)-2-hexenal . Abiotic stresses including low temperature, dehydration, and mechanical wounding, did not influence the (E)-2-hexenal content in intact tea leaves during withering, but regulated the proportions of (Z)-3-hexenal and (E)-2-hexenal in torn leaves by modulating CsHI at the transcript level. For the first time, this work reveals the formation of (E)-2-hexenal during tea processing and suggests that CsHI may play a pivotal role in tea flavor development as well as in plant defense against abiotic stresses.